2014
DOI: 10.1158/1535-7163.mct-13-0868
|View full text |Cite
|
Sign up to set email alerts
|

Leelamine Mediates Cancer Cell Death through Inhibition of Intracellular Cholesterol Transport

Abstract: Leelamine is a promising compound for the treatment of cancer; however, the molecular mechanisms leading to leelamine-mediated cell death have not been identified. This report shows that leelamine is a weakly basic amine with lysosomotropic properties, leading to its accumulation inside acidic organelles such as lysosomes. This accumulation leads to homeostatic imbalance in the lysosomal endosomal cell compartments that disrupts autophagic flux and intracellular cholesterol trafficking as well as receptor-medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(115 citation statements)
references
References 56 publications
5
107
0
1
Order By: Relevance
“…Therefore, optimally designed abietane diterpenoid compounds that specifically inhibit heme polymerization and kill malaria parasites may prove to be effective antimalarial drugs. Additionally, as reported previously for cancer cells (Kuzu et al, 2014), abietane diterpenoids having amine basicity may interfere with the cholesterol transport in parasites, causing membrane dysfunction and death. Therefore, based on the foregoing discussion, it appears that abietane diterpenoids target multiple functions in parasites.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…Therefore, optimally designed abietane diterpenoid compounds that specifically inhibit heme polymerization and kill malaria parasites may prove to be effective antimalarial drugs. Additionally, as reported previously for cancer cells (Kuzu et al, 2014), abietane diterpenoids having amine basicity may interfere with the cholesterol transport in parasites, causing membrane dysfunction and death. Therefore, based on the foregoing discussion, it appears that abietane diterpenoids target multiple functions in parasites.…”
Section: Resultssupporting
confidence: 52%
“…In cancer cells, it has been shown that dehydroabietylamine is lysomotropic, thus accumulates in lysosomes causing disruption of lysosomal compartments (Gowda et al, 2014; Kuzu et al, 2014). Dehydroabietylamine has also been shown to interfere with intracellular cholesterol transport, affecting membrane functions and leading to cell death.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations